2006
DOI: 10.1037/0735-7028.37.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Psychological needs and resources as perceived by rural and urban psychologists.

Abstract: Practicing psychologists in rural and urban Oregon were surveyed about their perceptions of psychological needs and resources in their communities. Both groups indicated the most salient unmet community needs as adequate access to appropriately trained medication prescribers, comprehensive psychological assessment services, and psychological services for children. When compared with urban communities, those in rural communities have more difficulties with accessing all professional services, and rural psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 11 publications
3
24
1
Order By: Relevance
“…There are long waiting lists of up to six months and extensive traveling distances for clients referred for neuropsychological services and clinicians working in the region. Furthermore, in their survey of psychologists practicing in Oregon, Campbell et al (2006) found that rural psychologists were more likely to report fewer available psychological assessment services than their urban counterparts. Due to limited specialist health care providers, both rural psychologists and neuropsychologists may rapidly …”
Section: Limited Resourcesmentioning
confidence: 97%
See 4 more Smart Citations
“…There are long waiting lists of up to six months and extensive traveling distances for clients referred for neuropsychological services and clinicians working in the region. Furthermore, in their survey of psychologists practicing in Oregon, Campbell et al (2006) found that rural psychologists were more likely to report fewer available psychological assessment services than their urban counterparts. Due to limited specialist health care providers, both rural psychologists and neuropsychologists may rapidly …”
Section: Limited Resourcesmentioning
confidence: 97%
“…Living and working in a rural or regional setting means longer travel distances for clients and clinicians, resulting in greater expenditure of time and money compared with metropolitan settings (Barbopoulos & Clark, 2003;Campbell et al, 2006). The greater cost of fuel is also evident in regional areas.…”
Section: Travel Distances and Costsmentioning
confidence: 97%
See 3 more Smart Citations